Flow regime and land cover changes in the Didessa sub-basin of the Blue Nile River, South-Western Ethiopia - Sima, Bizuneh (2011)

(untitled)
Defining stream flow and rainfall patterns over a period of different land use/cover changes and understanding the community’s knowledge on changes in the natural resources of the Didessa sub-basin of the Blue Nile River were the main areas which this study dealt with. Based on the availability of hydrological data 8 out of 14 different gauged catchments of Didessa sub-basin were selected for further analysis. For each of these sub-basins 15 to 27 years of daily stream flow and rainfall data were collected and analyzed. Simple time series graphs, temporal homogeneity test, correlation and regression analysis were used as the main tools for comparing and illustrating the hydrological and meteorological data. For assessing the change in the land use/cover of the study area, the Blue Nile Basin map, and satellite images were examined, previous studies were considered and a field visit to the study area was undertaken. To explore the views of local people, the Participatory Rural Assessment techniques of timeline, key informant interview and focus group discussion were employed. For most catchments the results revealed that the long term stream flow and rainfall trend and variations responded in accordance with the forest change of the area. In addition the already accepted hypothesis ‘forest clearing results in increasing stream flow’ was observed. The annual variability in stream flow and rainfall values was large for all catchments. However in all cases the variability in annual stream flow was much higher than in annual rainfall. It was noted that dry season flows and Base Flow indices values showed a non-significant change for all catchments. From the communities’ perception of changing natural resources, it was observed that most farmers are more aware on land use/cover dynamics than stream flow and climate changes. However farmers who use irrigation water for their farm plot appeared to have a better awareness in the stream flow changes than the ones who followed rain fed farming.